Hubungan Antara Manajemen Waktu Dengan Prestasi Belajar Mahasiswa Akademi Keperawatan RSPAD Gatot Soebroto Jakarta - Al- Bahra; Memed Sena Setiawan (JOURNAL EDUCATIONAL OF NURSING(JEN), 2019)
Learning achievement is the maximum effort achieved by someone after carrying out learning efforts. One of the factors that influence learning achievement is time management. The five aspects of time management used in this study are the preparation of a list of activities, priority scale, estimated time, time allocation, and evaluation. The purpose of this study was to determine the relationship between time management and student achievement in Nursing Academy Gatot Soebroto Jakarta Hospital. This research is an analytic study using survey method with cross sectional approach. The data used are primary data with a research instrument in the form of a questionnaire and secondary data about student learning achievement as seen from the value of student achievement index. The population in this study were all students of Nursing Academy Gatot Soebroto Jakarta Hospital in 2018, namely level 1 students. Level 1 students at the Nursing Academy Gatot Soebroto Jakarta Hospital who answered the questionnaire in the period 22-23 January 2018, namely 37 respondents. The results of this study indicate that the average respondents who think good of the 5 aspects of time management are 51.4% (19 people) and bad 48.6% (18 people). There are 75.7% of students (28 people) with sacred achievement between 3.26-3.5. The worse the time management, the lower the value of learning achievement (